Karakteristik Pembelajaran Kitab Kuning di Pondok Pesantren - Arman Paramansyah; Samsudin Siradj; Ade Irvi Nurul Husna; Ernawati Ernawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
This research is motivated by the unique facts about the existence of Sirojul Munir Islamic Boarding School in the villages in Bekasi City. The role of pesantren itself in general is as an Islamic Education Institution, Social Institution, and Islamic Da'wah Institute. The yellow book is one of the important elements of a boarding school besides the values ​​and leadership of the clerics. The yellow book has a significant position and role in the pesantren. Although it is still being taught, there is a suspicion of a shift in the teaching of the yellow book in the pesantren along with the adoption of educational systems outside the pesantren such as the madrasa and school systems. the distribution of questionnaires to santri as a sample of 50 people (santri who reside / stay at the pesantren), and the results obtained Bandongan and Sorogan are characteristic of the teaching system that is in the Pondok Pesantren Sirojul Munir. So with these two systems the students can compete to learn and motivate intrinsically and provide broad opportunities in problem solving. And from this system too, for students who have low self-confidence are slow in following the learning and teaching process Keywords: Pesantrean, kitab kuning , Sorogan and Bandongan Method.